Application of porous organosilica intercalated graphene oxide as the container of molybdate inhibitors for anticorrosive coatings. (15th January 2020) - Lin, Yunan; Chen, Rongrong; Zhang, Yanjun; Lin, Zhu; Liu, Qi; Liu, Jingyuan; Wang, Yanli; Gao, Liangtian; Wang, Jun
Abstract: Porous organosilica intercalated graphene oxide (p-GA) was synthesized via the two-step polymerization method using 1-(2-aminoethyl)-3- aminopropyltrimethoxysilane as monomer. The average pore diameter of p-GA was calculated to be 4.42 nm with the Barret–Joyner–Halenda (BJH) algorithm. Amino and imino groups on the surface of organosilica pore were served as loading sites for molybdate inhibitors(Al2 (MoO4 )3 ). The controlled release of inhibitor ions from the molybdate loading p-GA (p-GAMo) occurred during the hydrophilic transformation process of the organosilica pores. The p-GAMo was embedded in polyvinyl butyral (PVB) coating and applied on mild steel. The results show that p-GAMo/PVB coating has active inhibition performance and exhibits high impermeability. Graphical abstract: Image 1 Highlights: Porous organosilica intercalated graphene oxide was served as the container of Al2 (MoO4 )3 . Amino and imino groups on the surface of organosilica pore were used as loading sites. The active inhibition performance was confirmed in solution phase and coating respectively.